Comparison of thoracic and lumbar erector spinae muscle activation before and after a golf practice session - Sorbie, G. G.; Grace, F. M.; Gu, Y.; Baker, J. S.; Ugbolue, U. C. (Journal of Applied Biomechanics, 2017)
Lower back pain is commonly associated with golfers. The study aimed: to determine whether thoracic- and lumbar-erector-spinae muscle display signs of muscular fatigue after completing a golf practice session, and to examine the effect of the completed practice session on club head speed, ball speed and absolute carry distance performance variables. Fourteen right-handed male golfers participated in the laboratory-based-study. Surface electromyography (EMG) data was collected from the lead and trail sides of the thoracic- and lumbar-erector-spinae muscle. Normalized root mean squared (RMS) EMG activation levels and performance variables for the golf swings were compared before and after the session. Fatigue was assessed using median frequency (MDF) and RMS during the maximum voluntary contraction (MVC) performed before and after the session. No significant differences were observed in RMS thoracic- and lumbar-erector-spinae muscle activation levels during the five phases of the golf swing and performance variables before and after the session (p > .05). Significant changes were displayed in MDF and RMS when comparing the MVC performed before and after the session (p < .05). Fatigue was evident in the trail side of the erector-spinae muscle after the session. ABSTRACT FROM AUTHOR